Hands-On Data Analysis with NumPy and pandas Implement Python packages from data manipulation to processing - Miller, Curtis (Packt Publishing Limited, 2018)
bGet to grips with the most popular Python packages that make data analysis possible/bh2About This Book/h2ulliExplore the tools you need to become a data analyst/liliDiscover practical examples to help you grasp data processing concepts/liliWalk through hierarchical indexing and grouping for data analysis/li/ulh2Who This Book Is For/h2Hands-On Data Analysis with NumPy and Pandas is for you if you are a Python developer and want to take your first steps into the world of data analysis.